Self‐cleansing design of sewers: Definition of the optimum deposited bed thickness. (7th February 2019) - Safari, Mir Jafar Sadegh; Shirzad, Akbar
Abstract: Sediment deposits may influence the performance of the sewer systems. Sediments are the main store of pollutants which causes sewer systems overflows. In order to prevent the deposition of sediment in sewer systems, self‐cleansing design criteria are used. Among various criteria, "self‐cleansing with deposited bed" criterion is found appropriate for designing of large sewers. Allowing small thickness of deposited bed in large sewers decreases the required channel bed slope and construction costs. This study presents a bed load self‐cleansing model established on wide ranges of experimental data. Comparison of developed model with the existing models in the literature shows its higher performance on variety of data sources. Examples for the application of the model are presented, and design graphs and charts for different pipe sizes are proposed. As a result, the optimum deposited bed thickness is found 1%–5% of the pipe diameter; however, 1% is recommended for sewer pipes design. Practitioner points: Nondeposition sediment transport condition with a bed deposit criterion is found appropriate for large sewer pipe design. The precision of a model is linked to the ranges of experimental data and parameters used for the models development. The optimum range of deposited bed thickness can be adopted in the range of 1% to 5% of the pipe diameter.